História local e memória: o brinquedo de miriti como expressão cultural do município de Abaetetuba - CORREA, Tiago Ribeiro (2022)
This article aims to understand the importance of analyzing historical knowledge under different perspectives. Having as object of research the tradition of the production of miriti's toy, as it is one of the greatest cultural expressions in the municipality of AbaetetubaPA. The miriti toy is a form of handicraft that is characteristic of the municipality of Abaetetuba, its historical origin is vague, that is, it is only found in the orality of the people of Amazon (Loureiro 2020). Thus, this research is qualitative in nature and began with a bibliographical research emphasizing authors such as Adchie (2009) because his work “The danger of a unique history”, was of fundamental importance for the problematization of this research, Loureiro (2020) who researches and debates miriti's toy, Silva (2009), who debates about oral history as a tool for transmitting values, feelings, visions of world and culture, among others. Field research was carried out, using interview semi-structured as a data collection instrument, which was carried out with three residents of the municipality and that have a connection with the research object. The results obtained in allowed us to understand the importance of the miriti toy in the explicit understanding of the culture of the people of Abaetetuba, through the different versions of the stories told about he.